Gestión comunicacional y su impacto en el posicionamiento del Restaurante Los Girasoles del Cantón Buena Fe, año 2017. - Cerezo Bustamante, Kenia Evelyn (2017)
The research carried out is titled communication management and its incidence in the positioning of the restaurant has as main problem to know how the communicational management generates an impact in the positioning of the Restaurant Los Girasoles in Cantón Buena Fe ?, establishing as objectives to analyze the communication management to measure The positioning, investigate the current situation of the Restaurant, also determine the impact of the advertising image and design a proposal for a communication plan, proposing as methodology the field research and bibliographic documentary, as well as the inductive, deductive, analytical methods that helped To establish the results of the study of which determines that the current situation of the Restaurant Los Girasoles main weakness is the limited management in the communication to spread the brand of the company affecting its positioning in the target audience, plus the impact of public image Itaria in the knowledge that have the customers of the Restaurant is very low according to the manifested by the inhabitants who have not visualized a corporate image, also they are considered that there is no good advertising communication of the business, this encourages to propose the proposal of a Communication plan, it was recommended to improve the impact of the advertising image of Restaurant Los Girasoles by establishing the use of accessories that have the brand to increase market positioning and increase existing demand and use advertising and promotion tools, it is also necessary to establish A schedule to establish the communication plan where the tools are used in order to improve the level of sales. Furthermore, in the economic study it was determined that for the execution of the communicational plan of the Restaurant, it is necessary to invest US $ 3,950.00.